Dolly: a New Form of Transgenic Breedwealth. (1st November 1997) - Franklin, Sarah
Public debate in Britain surrounding the cloning of Dolly the sheep has primarily focused on the legitimacy of cloning humans, not sheep. This bracketing of the human question relies on a distinction between humans and animals belied by the very constitution of transgenic animals who are made with human DNA, such as Polly. Moreover, the ways in which human beings think about, manipulate and classify animals have distinct cultural consequences, for example in relation to cultural understandings of life, property, kinship and other forms of social interconnection. This article introduces the term 'breedwealth' to examine Dolly as a unique form of property in order to make some of these connections more visible.